2004
DOI: 10.1038/sj.onc.1207458
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of ubiquitin-conjugating enzyme CDC34 enhances anti-myeloma activity of Bortezomib/Proteasome inhibitor PS-341

Abstract: The ubiquitin-conjugating enzyme CDC34 (UBC3) is linked to cell cycle progression in diverse cell types; however, its role in multiple myeloma (MM) pathogenesis is unclear. Here, we show that CDC34 is highly expressed in patient MM cells and MM cell lines versus normal cells. Blocking CDC34 using a dominant-negative strategy enhances the anti-MM activity of Bortezomib/ Proteasome inhibitor PS-341, dexamethasone (Dex) and 2-Methoxyestradiol (2ME2). The expression of wild-type CDC34 reduces Dex-induced cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…26 CDC34 is highly expressed in multiple myeloma (MM) and associated with the growth and survival of MM cells. 27 An immunocytochemical study showed that FZD3 is strongly associated with CRC progression. 28 Additional studies on miR-4500 and its target genes may be helpful for understanding tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…26 CDC34 is highly expressed in multiple myeloma (MM) and associated with the growth and survival of MM cells. 27 An immunocytochemical study showed that FZD3 is strongly associated with CRC progression. 28 Additional studies on miR-4500 and its target genes may be helpful for understanding tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dex, 2ME2, and PS-341 treatments are associated with decreased CDC34 expression. Blocking CDC34 augments sensitivity to these therapies [67]. Targeting mitochondria may be an effective way to overcome conventional resistance and Velcade resistance in MM [68].…”
Section: Growth and Survival Factors Prevent Apoptosismentioning
confidence: 99%
“…Multiple myeloma is the most sensitive and the most responsive disease to proteasomal inhibitors, which implies that the UPP is critical for multiple myeloma pathophysiology. E1 [4], E2s such as CDC34 [5], E3s such as Mdm-2 [6] and SCF [7], and DUBs such as USP9X [8] are overexpressed and involved in multiple myeloma pathology. Furthermore, targeting such UPP components could sensitize MM cells susceptible to bortezomib-induced cell death [4,7].…”
Section: Introductionmentioning
confidence: 99%